(untitled) - M. Kawin Kumar (Academia Anesthesiologica International, 2020)
Background: Pain a common complaint often reported by post-operative cases. Fentanyl is one of the widely used short-term and rapid-response opioid drugs with addictive nature. Acetaminophen and another widely used pain killer without addictive property. Hence, this study was planned to compare the efficacy of fentanyl and acetaminophen in terms of reducing post-operative pain. Subjects and Methods : This randomized controlled trial was carried out in the department of anesthesiology among the surgical patients admitted in Sri Muthukumaran Medical College Hospital and Research Institute, Chennai from January 2019 to June 2019. A total of eighty cases were included and they were randomized and divided into two groups with forty cases in each group where group A received the drug fentanyl 1mcg/kg and group B received drug acetaminophen 1 gm intravenously during the second hour of their post-operative period. The pain was assessed using the VAS score. Results were analyzed using the Statistical Package for Social Sciences (SPSS) version 17. Results: Both fentanyl and acetaminophen groups were similar in terms of age, gender, different surgical procedures and complaints with no statistically significant difference, noted. However, postoperative pain scores were comparatively less in the fentanly group compared to the acetaminophen group during the sixth and twelfth postoperative hour but the pain scores were similar in both the groups at the twenty-fourth postoperative hour. Conclusion: Fentanyl can be used for the management of postoperative pain compared to acetaminophen, which reported comparatively fewer complaints.